ANALISIS EFIKASI DIRI SISWA KELAS VIII SMP NEGERI I SAMPIT TAHUN PELAJARAN 2016/2017 - Jayadi Jayadi; Alivermana Wiguna; Lensa Lensa (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
This study was conducted to know how self-efficacy to the eight grade students at SMP Negeri 1 Sampit in the Academic year of 2016/2017. The population in this study were all eight grade students at SMP Negeri 1 Sampit in the Academic year of 2016/2017, amounting to 259 students. The sampling technique used was proportional random sampling technique in which the samples were was 77 students. Data collection techniques used by is questionnaire. Data analysis technique used is quantitative descriptive. The research shows most students have efficacy in the learning process at medium category in the amount of 51 respondents (66.23%) consisting of 27 male respondents and 24 female respondents. For the group of respondents who have low self-efficacy categories were 10 respondents (12.99%), which consists of six respondents male and 4 female respondents. And only 16 respondents (20.78%) consisting of one male respondents and 15 female respondents who have high self-efficacy. Self-efficacy the eight grade students at SMP Negeri 1 Sampit, most tend to have self-efficacy with categories were as many as 51 respondents with a percentage of 66.23%.